Nano-bioremediation of heavy metals from environment using a green synthesis approach - Farah Aslam; Sumaira Mazhar (Institute of Advanced Engineering and Science, 2023)
The quality of human life is compromised due to the increased concentration of toxic heavy metals in air, water, and soil which is directly interacted with living life. Exceed levels of Cr, Cd, Cu, As, Zn, Pb, and Hg influence the living chain and not only causes human damage but also greatly effects animals, plants, and microorganisms. The consistent increase in drawbacks of traditional methods makes them a poor choice for the remediation of heavy metals. In comparison to that, the use of advanced technology at nano levels gives promising results. Many nanomaterials such as carbon nanotubes, nanofibers, nanoflowers, and nanoadsorbents of different metals such as copper, titanium, zinc, gold, silver, iron, cerium, and manganese use along with different biological materials increase the nano-bioremediation rate in the field of science and pose industrial and environmental applications. Being a cost-effective, eco-friendly, controllable nature of nano-bioremediation technology, they lack background knowledge, and handling at the commercial level. This review highlights different types of nanomaterials, how they are implemented in different application, their green synthesis approach, and the boon and bane of using nano-bioremediation technology in real-time.